ENERGETIC CHARGE OF AN INFORMATION PROCESS - Popova T.M. (Problems of the Regional Energetics, 2009)
Main laws of technical thermodynamics are universal and could be applied to processes other than thermodynamic ones. The results of the comparison of peculiarities of irreversible informational and thermodynamic processes are presented in the article and a new term “Infopy” is used. A more precise definition of “infopy” as an energetic charge is given in the article.